Physical and Mechanical Properties of Glulam from Sengon and Red Meranti Wood - Hamidi, Zikri (Fakultas Pertanian, Universitas Riau, 2024)
The high production of sawn timber has increased the demand for wood each year. This has created an imbalance between the growing demand for wood and the declining supply of wood from natural forests. To address this issue, innovations in wood engineering are necessary to meet future wood demand. One solution is to utilize wood to produce Glued Laminated Timber (glulam). This research uses sengon and red meranti wood, forming three models: Model A, Model B, and Model C, with sizes of 120 x 5 x 1 cm and 120 x 3 x 1 cm. The objective of this study on glulam from sengon and red meranti wood is to determine the characteristics of its physical and mechanical properties. The highest density for physical properties is produced by Model B glulam, which is 0.579 g/cm³, the highest moisture content is produced by Model C glulam, which is 14.43%, delamination in cold water ranges from 12.08% to 32.08%, and in boiling water ranges from 22.25% to 44.63%. The highest MOE and MOR tests are shown by Model B and Model A. The results obtained for the MOE of Model B are 10,960.194 MPa and the MOR of Model A is 74.677 MPa.Key words: Glulam, Red Meranti Wood, Sengon Wood